Financial Crisis and Stock Return Volatility of the JSE General Mining Index: GARCH Modelling Approach: Array - Muzindutsi, Paul-Francois; Obalade, Adefemi A.; Gaston, Rugiranka Tony (The Journal of Accounting and Management, 2020)
The aim of this article is to model the return volatility of the JSE mining sector and analyse how changes in the return volatility were affected by the 2008 financial crisis. The GARCH, EGARCH and GJR-GARCH are estimated in mean with the Student’s t-distribution. To account for the 2008 financial crisis, the sample period, which included daily stock index returns from July 1995 to June 2018, was divided into three sub-periods. From the results, the best-fit model for the three sub-periods was found to be GJR-GARCH (1, 1). The results revealed that the level of volatility varies across the three sub-periods with the highest reported pre-crisis and the lowest volatility during crisis. This article found that the level of volatility decreased significantly during crisis, but began to rise after the crisis, although not rising to the pre-crisis level. This implies that the crisis increased the mining investors’ risk aversion. Fundamentally, the magnitude of the volatility is not similar across three sub-periods. Such variation suggested different reactions of investors to new information. The fluctuation in volatility proved that the 2008 financial crisis affected JSE mining investors’ attitudes towards overall risk.